Artistic variants in botanical decoration Designs of the opening of the Holy Qur’an "model" (Journal of the College of Basic Education, 2023)
The researcher drew the idea of the current study from the importance of developing the applied side and studying the technical variables of plant decorative elements in detail, as it seeks to contribute to the development and maturation of design awareness among researchers and craftsmen, and accordingly, the researcher identified the problem of his research by asking the following question:What are the artistic variables in the plant motifs of the designs of the opening of the Holy Qur’an? .The research aimed to answer this question by studying the technical variables through the detailed study of the variables of the decorative unit (sepals - vase), and identifying them for the purpose of analysis, as well as identifying the technical variables of the decorative elements within the design structure of the opening of the Holy Qur’an.The theoretical framework dealt with the topics according to two sections:1- The first topic / the emergence and development of the decorations of the Holy Qur’an.2- The second topic / artistic variables in plant decorations, and these plant decorations were divided according to their variable shapes and artistic elements into two patterns, which are sepals and floral motifs.The researcher also followed the analytical descriptive approach to reach results that achieve his goals and solve his problem, and the sample was chosen in an intentional manner to choose the models that serve the current research, and given the similarity with other design forms or decorative elements, so the researcher identified (3) samples for the opening of the Holy Qur’an, and he has It was chosen according to its patterns. The first sample is designs for floral motifs, the second sample is designs for cup motifs, and the third sample is designs for mixed motifs. It has been presented to experts to ensure its validity in achieving the goals.The researcher reached a number of results that can be summarized according to the sequence of the analysis paragraphs